Resolving the puzzle of single-atom silver dispersion on nanosized γ-Al2O3 surface for high catalytic performance - Wang, Fei; Ma, Jinzhu; Xin, Shaohui; Wang, Qiang; Xu, Jun; Zhang, Changbin; He, Hong; Cheng Zeng, Xiao (Nature communications, 2020)
Ag/γ-Al 2 O 3 is widely used for catalyzing various reactions, and its performance depends on the valence state, morphology and dispersion of Ag species. However, detailed anchoring mechanism of Ag species on γ-Al 2 O 3 remains largely unknown. Herein, we reveal that the terminal hydroxyls on γ-Al 2 O 3 are responsible for anchoring Ag species. The abundant terminal hydroxyls existed on nanosized γ-Al 2 O 3 can lead to single-atom silver dispersion, thereby resulting in markedly enhanced performance than the Ag cluster on microsized γ-Al 2 O 3 . Density-functional-theory calculations confirm that Ag atom is mainly anchored by the terminal hydroxyls on (100) surface, forming a staple-like local structure with each Ag atom bonded with two or three terminal hydroxyls. Our finding resolves the puzzle on why the single-atom silver dispersion can be spontaneously achieved only on nanosized γ-Al 2 O 3 , but not on microsized γ-Al 2 O 3 . The obtained insight into the Ag species dispersion will benefit future design of more efficient supported Ag catalysts. Detailed atom-level anchoring mechanism of Ag species on γ-Al 2 O 3 is largely unknown for the widely used Ag/γ-Al 2 O 3 catalyst. Here, the authors demonstrate that single-Ag atom can be only anchored by the terminal hydroxyls on the (100) surfaces of γ-Al 2 O 3 through consuming two or three terminal hydroxyls.